RESEARCH ON DYNAMIC RESPONSE OF SUPER LARGE FLOATING WIND TURBINE UNDER WIND-WAVE MISALIGNMENT - LIU YiMing; WANG Bo; LIU QingSong; LI Chun; DING QinWei (Jixie qiangdu)
Taking the DTU 10 MW wind turbine as the research object, the OO-Star semi-submersible platform floating wind turbine model is established, based on the blade element momentum theory and the radiation/diffraction theory to solve the wind load and wave load respectively, and the dynamic response of floating wind turbines under different environmental load directions is simulated, and the impact of different environmental load incident angles on its response characteristics is compared and analyzed. The results show that the incident angle of turbulent wind has a greater influence on the response of floating wind turbines to surge, pitch and yaw, while the incident angle of wave has a great influence on the sway and roll response. The heave response hardly changes with the turbulent wind and wave incident angle. As the incident angle of turbulent wind increases, the average power of floating wind turbines drops sharply, while the incident angle of waves has almost no effect on its average power. In addition, in the mooring system, the mooring tension of No.1 increases gradually with the increase of the incident angle of turbulent wind and wave, while that of No.2 mooring decreases gradually, while that of No.3 mooring increases first and then decreases with the increase of incident angle of turbulent wind, and increases gradually with the increase of incident angle of wave.